2020
DOI: 10.1542/peds.2020-1134
|View full text |Cite
|
Sign up to set email alerts
|

State and Local Government Expenditures and Infant Mortality in the United States

Abstract: BACKGROUND AND OBJECTIVES: Evidence suggests that government expenditures on non-health care services can reduce infant mortality, but it is unclear what types of spending have the greatest impact among groups at highest risk. Thus, we sought to quantify how US state government spending on various services impacted infant mortality rates (IMRs) over time and whether spending differentially reduced mortality in some subpopulations. METHODS:A longitudinal, repeated-measures study of US state-level infant mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…29 Similar mortality trends have also been observed in the USA, with similar timings but different underlying characteristics, these characteristics being heavily influenced by midlife deaths related to drug and alcohol abuse. 30 There is some American evidence on the effect of local services on mortality, 31,32 but the relevance of these studies in international contexts is uncertain IMD quintile Q1 least deprived Q5 most deprived because of the underlying differences in health systems and local service delivery. Several strengths of our analysis enhance its validity.…”
Section: Discussionmentioning
confidence: 99%
“…29 Similar mortality trends have also been observed in the USA, with similar timings but different underlying characteristics, these characteristics being heavily influenced by midlife deaths related to drug and alcohol abuse. 30 There is some American evidence on the effect of local services on mortality, 31,32 but the relevance of these studies in international contexts is uncertain IMD quintile Q1 least deprived Q5 most deprived because of the underlying differences in health systems and local service delivery. Several strengths of our analysis enhance its validity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report shows that governmental spending minimizes [123][124][125] the existing inequalities. For example, some research suggests that the Affordable Care Act (ACA) has reduced inequalities [126][127][128][129][130][131][132], in part because some of these applied policies may have larger effects on the underserved than privileged populations [133].…”
Section: Discussionmentioning
confidence: 99%
“…38 One study found evidence that state budgeting might partially mediate the association between party majority in state legislatures and infant health. 39 Republican administrations are also known to deregulate the gun industry 40 and to correlate with higher suicide and homicide rates. 41 In addition, policies that shape the electorate in ways that increase Republican electoral advantage by suppressing the vote of those who suffer the greatest health inequities-the poor and minorities-could influence to which voters elected Republicans feel beholden when shaping their agenda and policy priorities.…”
Section: Discussionmentioning
confidence: 99%